Building the extended enterprise: key collaboration factors - Braziotis, Christos; Tannock, James (The international journal of logistics management, 2011)
Purpose - The purpose of this paper is to explore supply chain collaboration issues in the extended enterprise (EE) to develop a more complete understanding of the nature and effectiveness of collaboration in the transition towards, but also within, the EE paradigm.Design methodology approach - The paper presents results from a three-company case study focusing on the civil aerospace industry, with all companies taking part in an EE. The research involved obtaining and systematically analysing a diversity of interview data and company documents to assist in the development of theory, which was subject to a systematic validation process.Findings - The authors propose a taxonomy, which, first, assists in understanding the transition towards the EE and supports a distinction between sets of factors that affect the effectiveness of collaboration, termed the "contractual" and "engaging" factors. Second, it assists in understanding the dynamic, complex nature of the EE paradigm and suggests a further breakdown of the "engaging" factors into "enabling" and "enhancing" sub-sets.Practical implications - The taxonomy assists in comprehending the EE concept and can also help to provide a road map in the transition towards and development within this paradigm. The description of the factors and their interrelationships suggest key areas that managers may wish to consider to enhance the effectiveness of collaboration among participant organisations.Originality value - This is an empirically-based paper that presents new understanding about the EE paradigm, focussing especially on the effectiveness of collaboration among members, and using a multidisciplinary approach which draws upon strategic, operations and knowledge management fields.